Association of α1-antichymotrypsin deficiency with milder lung disease in patients with cystic fibrosis. Issue 1 (1st January 2001) - Mahadeva, R; Sharples, L; Ross-Russell, R I; Webb, A K; Bilton, D; Lomas, D A
Abstract : BACKGROUND: Cystic fibrosis (CF) is characterised by an excess of free proteinases that destroy lung tissue. Despite this, previous studies have shown that patients with CF with a mild deficiency variant of the proteinase inhibitor α1 -antitrypsin have less, rather than more, severe pulmonary disease. Alpha1 -antichymotrypsin is another important serine proteinase inhibitor that protects the lung against proteolytic attack, and point mutations in the α1 -antichymotrypsin gene that result in plasma deficiency are associated with chronic obstructive pulmonary disease. METHODS: The effect of α1 -antichymotrypsin deficiency and the –15 α1 -antichymotrypsin signal peptide genotype on lung function was assessed in patients with CF. RESULTS: One hundred and fifty seven patients with CF were screened and 10 were identified with a plasma deficiency of α1 -antichymotrypsin (plasma concentration <0.2 g/l). In a multivariate analysis these individuals had significantly less severe lung disease than those who had normal or raised levels of α1 -antichymotrypsin: forced expiratory volume in one second (FEV1 ) 69.9% predicted versus 53.2% predicted (p=0.04) and chest radiographic score of 7.2 versus 9.7 (p=0.03) for those with and without α1 -antichymotrypsin deficiency, respectively. The –15 signal peptide genotype did not affect plasma levels, but the –15 Ala/Ala signal peptide genotype was over-represented in individuals with CF compared with healthy blood donor controls. CONCLUSION: These data indicate that deficiency of α1 -antichymotrypsin is associated with less severe pulmonary disease in patients with CF, and support our previous observations that mild genetic deficiency of a proteinase inhibitor is associated with an improved outcome.